The Transect as a Method for Mapping and Narrating Water Landscapes: Humboldt’s Open Works and Transareal Travelling - Lisa Diedrich; Gini Lee; Ellen Braae (NANO, 2014)
In current urban design and landscape architecture practice, designers often address sites from static and material perspectives: as empty grounds where new design inventions are played out at the whim of their creators. Despite such design works claiming site specificity as their guide, generic outcomes that ignore or overlook local conditions abound, lacking response to ephemeral yet essential site properties such as temporal dynamics and atmospheric encounters. The focus of this NANO note seeks methods for site exploration to inform site transformation through representing the narrative, ephemeral, and dynamic qualities of places that could contribute to open work design approaches.